Mononuclear Heterocyclic Rearrangement of 5-Arylisoxazole-3-hydroxamic Acids into 3,4-Substituted 1,2,5-Oxadiazoles - Potkin, Vladimir I.; Petkevich, Sergey K.; Lyakhov, Alexander S.; Ivashkevich, Ludmila S. (Synthesis, 2013)
By a series of successive transformations, 5-arylisoxazole-3-carboxylic acids (aryl = phenyl, p-tolyl, 2,5-dimethylphenyl) have been converted into 5-arylisoxazole-3-hydroxamic acids, which undergo rearrangement by the action of aqueous KOH to form 3,4-substituted 1,2,5-oxadiazoles. The structure of one of them, 1-(2,5-dimethylphenyl)-2-(4-hydroxy-1,2,5-oxadiazol-3-yl)ethanone, has been confirmed by single crystal X-ray analysis.
Keywords: isoxazoles; 1,2,5-oxadiazoles; furazans; rearrangement; crystal structure; hydroxamic acids